Coexisting sub-zero temperature and relative humidity influences on sensors and composite material. (15th March 2021) - Majewska, Katarzyna; Mieloszyk, Magdalena; Jurek, Michal; Ostachowicz, Wieslaw
Abstract: The paper is focused on coexisting influence of sub-zero temperature and different relative humidity levels on fibre Bragg grating (FBG) sensors and glass composite. The analyses were performed at different environmental (dry/wet) and sensors boundary ('free', woven, glued, embedded) conditions. Strain values determined for sub-zero temperatures differ among sensors, even these embedded into the material. The influence of wet conditions on the measured strain values was stronger for −50 °C than −20 °C. The influence of phase change of water (in the container)/moisture (inside the material) from liquid to the solid state was taken into consideration. Additionally, the application of THz spectroscopy allowed to observe the internal composite structure changes due to the coexisting influence of temperature (from sub-zero to room temperature) and different humidity levels. A theoretical model based on the theory of laminates was presented and discussed.